Metazoan diversity in Chilean hypersaline lakes unveiled by environmental DNA - Saccò, Mattia; Campbell, Matthew A.; Aguilar, Pablo; Salazar, Gonzalo; Berry, Tina E.; Heydenrych, Matthew J.; Lawrie, Angus; White, Nicole E.; Harrod, Chris; Allentoft, Morten E. (Frontiers in Ecology and Evolution, 2025)
Saline and hypersaline wetlands are biodiversity hotspots for metazoans such as aquatic invertebrates and wading birds. However, the survival of these habitats and their biota is increasingly threatened by a combination of pressures from climate change and extractive processes. With the goal of improving conservation efforts in hypersaline ecosystems, this study tests the use of eDNA methods for metazoan biomonitoring. We employed a multi-assay approach utilizing three genetic markers—12S rRNA, 18S rRNA, and COI —to analyze biodiversity in sediment and water. Samples were collected from three hypersaline lakes in Northern Chile: Salar de Atacama (Laguna Puilar), Salar de Pujsa, and Salar de Tara. eDNA outputs were also compared with results generated from aquatic macroinvertebrate assessments using kick-nets. Our eDNA analyses revealed a total of 21 and 22 taxa across the three hypersaline lakes in sediment and water, respectively. The highest diversity was found in Salar de Tara (15 taxa within sediment and 13 taxa from water). Our multi-assay design detected a range of resident hypersaline taxa with different conservation status, spanning from rotifers to endangered snails, to amphipods and flamingos. Macroinvertebrate data via kick-net surveys further validated Salar de Tara as the most biodiverse system. Compared to net-based assessments, eDNA analysis allowed more refined taxonomic assignments for copepods and ostracods, while certain taxa such as Ephydridae or Hirudinea were not detected through molecular tests. Overall, this study provides evidence that eDNA is an effective tool to elucidate fine scale taxa assemblages and can refine conservation efforts in hypersaline lakes.